Potential of Artocarpus heterophyllus Seed Powder in the Adsorption of Chromium(VI) from Aqueous Solution - Lubanga, Cranmer; Ntambi, Emmanuel; Adaku, Christopher (Journal of Water Resource and Protection, 2017)
The potential of Artocarpus heterophyllus (Jackfruit) seed powder in adsorption of chromium(VI) from aqueous solution was studied using batch technique. The performance of the adsorption process was evaluated against contact time, pH, adsorbent dose, temperature and initial chromium(VI) ion concentration. The influence of the presence of interfering anionic species including chlorides, nitrates and sulphates on the adsorption process was also evaluated. The adsorption of chromium(VI) by Jackfruit seed powder reached equilibrium after 60 minutes. Higher chromium(VI) adsorption was observed at lower pH values with maximum removal (96.05%) occurring at pH 2. A great deal of adsorption (92.53%) was observed at the adsorbent dosage level of 1.0 g/100 ml solution. There was an improvement in the adsorption process when the temperature was increased from 25˚C (95.35%) to 60˚C (99.56%) followed by a decrease to 98.76% at 70˚C. Adsorption decreased with increasing initial chromium(VI) ion concentration. The adsorption followed both Freundlich and Langmuir adsorption models with correlation coefficients of 0.998 and 0.994 respectively, and Qm of 0.57 mg/g. The presence of nitrate and chloride ions significantly lowered the adsorption, with all the p values < 0.05 at 95% significant level. Meanwhile, the presence of sulphate ions enhanced chromium(VI) adsorption as most of the p values were >0.05. From the obtained Qm, Jackfruit Seed Powder is a good adsorbent for the aqueous solutions of Cr(VI). The adsorption process is slowed by the presence of the interfering anionic species.
Keywords: Chromium(VI); Artocarpus heterophyllus; Adsorption; Interfering Ions